The realness of things past ancient Greece and ontological history - Anderson, Greg 1962- (Oxford University Press, 2018)
"To make the case for this alternative paradigm, the book engages with currents of thought in many different intellectual provinces, from anthropology and postcolonial studies to the sociology of science and quantum physics. And to demonstrate how the new paradigm might work in practice, it uses classical Athens as its primary case study. The book is expressly written to be accessible to a non-specialist, cross-disciplinary readership" ...
Includes bibliographical references and index
Keywords: History -- Philosophy; Historische Methode; Geschichtsschreibung; Geschichtsbild; Demokratie; Politische Philosophie; Rezeption; Ontologie; Greece -- History -- Athenian supremacy, 479-431 B.C. -- Historiography; Athen; Griechenland -- Altertum